Vestibular-Evoked Myogenic Potential Testing in Vestibular Localization and Diagnosis - Taylor, Rachael L.; Welgampola, Miriam S.; Nham, Benjamin; Rosengren, Sally M. (Seminars in Neurology, 2020)
Vestibular-evoked myogenic potentials (VEMPs) are short-latency, otolith-dependent reflexes recorded from the neck and eye muscles. They are widely used in neuro-otology clinics as tests of otolith function. Cervical VEMPs are recorded from the neck muscles and reflect predominantly saccular function, while ocular VEMPs are reflexes of the extraocular muscles and reflect utricular function. They have an important role in the diagnosis of superior canal dehiscence syndrome and provide complementary information about otolith function that is useful in the diagnosis of other vestibular disorders. Like other evoked potentials, they can provide important localizing information about lesions that may occur along the VEMP pathway. This review will describe the VEMP abnormalities seen in common disorders of the vestibular system and its pathways.
Keywords: VEMP; otolith; diagnosis; localization